2022
DOI: 10.1021/acs.inorgchem.2c00943
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of Cr3+ as a Reductant in the Hydrothermal Synthesis of CuCrO2 Delafossite

Abstract: The synthesis of nanocrystalline, p-type delafossite metal oxides (CuMO2) via hydrothermal methods has been explored for a variety of energy conversion and storage applications. However, isolation of the pure phase ternary product is challenging due to the facile growth of unwanted, binary byproducts (CuO, Cu2O, and M2O3) which could ultimately influence the optoelectronic properties of the resulting nanocrystals. Here, we report on the optimized hydrothermal synthesis of CuCrO2 nanocrystals to limit the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 33 publications
(47 reference statements)
4
6
0
Order By: Relevance
“…Figure S1 shows powder diffractograms collected pre‐ and post‐annealing to confirm the integrity of the CuCrO 2 solid. XPS studies on post‐annealed CuCrO 2 films also supported the conclusion that Cu 2+ sites are present to charge compensate for Cu + vacancies seen from ICP results, as previously reported [30] . Figure S2 shows Cu XPS spectra where the Cu region indicates a peak at 936.7 eV assigned to Cu 2+ .…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Figure S1 shows powder diffractograms collected pre‐ and post‐annealing to confirm the integrity of the CuCrO 2 solid. XPS studies on post‐annealed CuCrO 2 films also supported the conclusion that Cu 2+ sites are present to charge compensate for Cu + vacancies seen from ICP results, as previously reported [30] . Figure S2 shows Cu XPS spectra where the Cu region indicates a peak at 936.7 eV assigned to Cu 2+ .…”
Section: Resultssupporting
confidence: 83%
“…CuCrO 2 nanocrystals were synthesized following a previously published procedure from our group. [30] Solid material produced from that study were further used for experiments reported here, thus some characterization methods have been previously reported. Powder diffractograms are shown in Figure 2a for the synthesized CuCrO 2 nanocrystals after washing in 0.5 M NH 4 OH for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations